2015
DOI: 10.1016/j.ajhg.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

THOC2 Mutations Implicate mRNA-Export Pathway in X-Linked Intellectual Disability

Abstract: Export of mRNA from the cell nucleus to the cytoplasm is essential for protein synthesis, a process vital to all living eukaryotic cells. mRNA export is highly conserved and ubiquitous. Mutations affecting mRNA and mRNA processing or export factors, which cause aberrant retention of mRNAs in the nucleus, are thus emerging as contributors to an important class of human genetic disorders. Here, we report that variants in THOC2, which encodes a subunit of the highly conserved TREX mRNA-export complex, cause syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 48 publications
5
77
1
Order By: Relevance
“…THOC2 is the human ortholog of the yeast Tho2 protein and, as the largest subunit of TREX, is proposed to act as a scaffold for the formation of the complex [53]. THOC2 is an essential component for maintaining TREX function in humans [15,42], and mutations in the THOC2 gene are associated with intellectual disabilities [22,54]. The conserved THOC3 (hTEX1) protein has been recently established as a component of the THO subcomplex in TREX and contains WD40 repeat motifs that allow multiple protein interactions (Figure 2) [10,15].…”
Section: The Composition Of Trexmentioning
confidence: 99%
See 1 more Smart Citation
“…THOC2 is the human ortholog of the yeast Tho2 protein and, as the largest subunit of TREX, is proposed to act as a scaffold for the formation of the complex [53]. THOC2 is an essential component for maintaining TREX function in humans [15,42], and mutations in the THOC2 gene are associated with intellectual disabilities [22,54]. The conserved THOC3 (hTEX1) protein has been recently established as a component of the THO subcomplex in TREX and contains WD40 repeat motifs that allow multiple protein interactions (Figure 2) [10,15].…”
Section: The Composition Of Trexmentioning
confidence: 99%
“…In the first class, missense mutations in the THOC2 gene cause syndromic intellectual disability [22]. Additionally, a de novo translocation event in the vicinity of THOC2 on the X-chromosome has been described in a child with cerebellar hypoplasia, ataxia and retardation [54].…”
Section: Biological Roles Of Trexmentioning
confidence: 99%
“…Furthermore, genetic analysis demonstrated that food avoidance of prmt-1 null mutants can be blocked by silencing either thoc-2 or inx-17, both of which have been recently identified as mitochondrial surveillance genes (16). THOC-2 has been shown to be an mRNA-binding protein facilitating the nuclear export of mRNA and required for proper neuronal development (42), while the function of INX-17, which is expressed abundantly in interneurons, is still unknown. Although the detailed mechanisms underlying food avoidance by mitochondrial dysfunction remain unclear, it is possible that the loss of asymmetric arginine dimethylation induces this defensive behavior through the same pathway and neuronal circuits as those induced by inhibition of OXPHOS components (e.g., isp-1), because the stress responses triggered in the two events are similar (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal translocation and inactivation of THOC2, a subunit of the core TREX complex, leads to cognitive impairment, cerebellar hypoplasia, and congenital ataxia in humans[278]. Additionally, missense mutations in THOC2 have been implicated in fragile X syndrome [279], and mutations in a second THO subunit, THOC6, lead to intellectual disabilities [280]. Moreover, loss of function mutations in Gle1 results in ALS [281] and fetal motor neuron disease [282].…”
Section: Impaired Nuclear Exportmentioning
confidence: 99%